Lexical errors in second language scientific writing: Some conceptual implications - Carrió-Pastor, María Luisa; Mestre-Mestre, Eva María (International Journal of English Studies, 2013)
Nowadays, scientific writers are required not only a thorough knowledge of their subject field, but also a sound command of English as a lingua franca. In this paper, the lexical errors produced in scientific texts written in English by non-native researchers are identified to propose a classification of the categories they contain. This study will enable researchers to improve their writing and facilitate smoother communication among international writers. In addition, establishing the causes of these errors may enable the recurrent pattern to be identified and the necessary guidelines for their correction to be drawn up. These data may be able to illuminate the processes followed by non-native speakers of English when learning new words, and thereby facilitate the avoidance of errors and the identification of the mechanisms which can permit the correct production of the specialised lexicon. doi: http://dx.doi.org/10.6018/ijes/14/1/154361